Upaya Pencegahan Gangguan Postpartum Mood Sejak Kehamilan di Masa Pandemi Covid-19 - Dwi Sri Handayani; Yuni Purwati (Universitas Muhammadiyah Semarang, 2021)
In these recent days, Covid-19 becomes the global health problem. One of the effects of the Covid-19 pandemic is a mother’s anxiety during pregnancy and the puerperium. This anxiety can put mothers at risk for postpartum mood disorders. Prevention of postpartum mood disorders can be done from the pregnancy time with preparatory education in dealing with the mothers’ roles for their babies. As an effort to maintain health protocols in this pandemic era, services to pregnant and postpartum women during the Covid-19 pandemic can be done through online communication media. This service aims to determine the data of the risk of postpartum mood disorders or postpartum depression since pregnancy and prepare mothers to welcome their role as postpartum mothers.The service method was carried out by screening the risk of postpartum mood disorders using the Edinburgh Postnatal Depression Scale (EPDS) and health education about the management of postpartum care for mothers and babies to the third-trimester pregnant women through online media. The results showed that six pregnant women (42.86%) had no risk of depression; seven pregnant women (50%) indicated that depression might occur, and one pregnant woman (7.14%) indicated the possibility of depression. During the counselling session, the mothers were less active in group discussions in online media and some mothers preferred private consultations. In addition, the mothers also expressed their desire to learn materials about pregnancy exercise, postpartum exercise, and lactation management during the outreach activities. From the results of screening using EPDS regarding postpartum mood disorders since pregnancy, it was found that there was a risk of depression during pregnancy and a possible risk of postpartum depression. Online health education for postpartum care management for postpartum mothers and babies as an effort to prevent postpartum mood since pregnancy during the Covid-19 pandemic can be done using the online method